MTOR inhibition potentiates cytotoxicity of Vγ4 γδ T cells via up‐regulating NKG2D and TNF‐α. Issue 5 (2nd June 2016) - Cao, Guangchao; Wang, Qian; Li, Guangqiang; Meng, Ziyu; Liu, Hui; Tong, Jiyu; Huang, Wanjun; Liu, Zonghua; Jia, Yanqiong; Wei, Jun; Chi, Hongbo; Yang, Hengwen; et al.
Abstract : Strategy to improve γδ T cells based cancer immunotherapy by suppressing mTOR signaling. Abstract : γδ T cells play a critical role in early anti‐tumor immunity and perform cytotoxicity via NKG2D for recognition and multiple cytotoxic factors for tumor killing. Recent studies have demonstrated pivotal roles of mTOR‐mediated metabolism in the maturation, differentiation, and effector function of diverse immune cells, including DCs, NK cells, CD4 + T cell subsets, and CD8 + T cells, but the role of mTOR signaling in γδ T cells is barely known. Here, we showed that suppressing mTOR signaling in in vitro‐expanded Vγ4 γδ T cells via the mechanistic inhibitor rapamycin enhanced their cytotoxicity against multiple tumor cell lines, and these cells performed better tumor‐suppressing effects upon adoptive therapy. Further investigation revealed that elevated cytotoxicity was a result of up‐regulation of NKG2D and TNF‐α. Moreover, rapamycin treatment significantly decreased the expression of CISH and increased pSTAT5. The inhibition of STAT5 pathways via siRNA interference or a specific inhibitor eliminated the up‐regulation of NKG2D and TNF‐α in rapamycin‐treated Vγ4 γδ T cells. These results uncovered an important role of mTOR signaling in the cytotoxic effector function of γδ T cells and provided a potential strategy to improve γδ T cell‐based cancer immunotherapy.